Analisis tentang status anak pada pasangan murtad perspektif UU No. 16 Tahun 2019 dan Mazhab Syafi’i - Affan, Moh. Sa’i; Holil, Holil (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
This research addresses the legal status of children born to a couple in which one partner committed apostasy after marriage. The issue arises when a marriage, initially based on Islamic principles following the conversion of one Christian partner to Islam, later becomes complicated as one spouse returns to their previous religion. This situation leads to questions regarding the legitimacy of children born before and after the apostasy, especially in the context of Indonesian Law No. 16 of 2019, which states that a marriage is valid only if conducted according to the religious laws of each party. This study employs a normative legal research method with a comparative approach, focusing on literature review and documentation techniques. The analysis compares the perspectives of Indonesian positive law and the Shafi'i school of Islamic jurisprudence on the child’s status. The findings indicate that, under Law No. 16 of 2019, the children are considered legitimate despite the marriage's invalidity due to differences in religious belief. From the Shafi'i perspective, if apostasy occurs before consummation (dukhul), the marriage is immediately annulled; if it occurs after consummation, the marriage remains valid until the completion of the 'iddah period. In both cases, children retain legitimate status. However, regarding custody, the law does not provide explicit guidance, whereas in the Shafi'i school, custody is automatically granted to the Muslim parent.